1983
DOI: 10.1042/bj2130679
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of tyrosine and lysine residues in native and modified horse cytochrome c

Abstract: 1H-n.m.r. and 13C-n.m.r. spectroscopy of horse cytochrome c and 1H-n.m.r. spectroscopy of the lysine-modified proteins N epsilon-acetimidyl-, N epsilon-amidino-, N epsilon-trifluoroacetyl- and N epsilon-maleyl-cytochrome c have shown that, although the lysine modifications do not greatly perturb the protein structure at pH7 and 27 degrees C, at higher temperature or at alkaline pH some parts of the structure are markedly perturbed. At pH7 and 27 degrees C the region of the protein about Ile-57 is affected in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The pH-dependence of the Ile-57 resonances of tuna ferrocytochrome c is similar both to the temperature-dependence of the Ile-57 resonances of tuna and horse ferrocytochromes (Moore & Williams, 1980c,e) and to the pH-dependence of the Ile-57 5CH3 resonance of horse ferrocytochrome c (Boswell et al, 1983); with increasing pH or temperature, below the denaturation point, the 5CH3 resonance shifts downfield and the y-CH3 resonance shifts upfield. A large increase in linewidth only occurs for the pH-dependence.…”
Section: Ofhorse Cytochrome Csupporting
confidence: 59%
See 2 more Smart Citations
“…The pH-dependence of the Ile-57 resonances of tuna ferrocytochrome c is similar both to the temperature-dependence of the Ile-57 resonances of tuna and horse ferrocytochromes (Moore & Williams, 1980c,e) and to the pH-dependence of the Ile-57 5CH3 resonance of horse ferrocytochrome c (Boswell et al, 1983); with increasing pH or temperature, below the denaturation point, the 5CH3 resonance shifts downfield and the y-CH3 resonance shifts upfield. A large increase in linewidth only occurs for the pH-dependence.…”
Section: Ofhorse Cytochrome Csupporting
confidence: 59%
“…A large increase in linewidth only occurs for the pH-dependence. The cause of the pH-induced chemical-shift variation is the ionization of a lysine residue (Boswell et al, 1983 that produced by a variation in temperature: the position of Ile-57 with respect to the surrounding amino acid side chains is perturbed.…”
Section: Ofhorse Cytochrome Cmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of parameters that are directly affected by the pK of basic side-chains, such as binding to ion-exchange resins, there are no significant differences. In contrast, the guanidyl or acetimidyl proteins show small decreases in biological activity and redox potential [8], which in the acetimidyl case, at least, is associated with a minor conformational change [33]. Wallace [7] has shown that this is a consequence of the modification of lysine residue 53, and no other.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the alkaline form of cytochrome c is stabilized by chemical modifications of amino acids, cleavage of certain parts of the polypeptide chain, perturbation of interactions inside the heme crevice, interactions with anionic phospholipids, increased temperature, and the presence of denaturants, resulting in a lower pK a (29,41,(67)(68)(69)(70)(71)(72). Such conditions are associated with local or global destabilization of the protein fold induced by the deprotonation of one or more residues.…”
Section: Discussionmentioning
confidence: 99%